Use of oral corticosteroids and risk of fractures. - Van Staa, T; Leufkens, H; Abenhaim, L; Zhang, B; Cooper, C (2000)
Treatment with oral corticosteroids is known to decrease bone density but there are few data on the attendant risk of fracture and on the reversibility of this risk after cessation of therapy. A retrospective cohort study was conducted in a general medical practice setting in the United Kingdom (using data from the General Practice Research Database [GPRD]). For each oral corticosteroid user aged 18 years or older, a control patient was selected randomly, who was matched by age, sex, and medical practice. The study comprised 244,235 oral corticosteroid users and 244,235 controls. The average age was 57.1 years in the oral corticosteroid cohort and 56.9 years in the control cohort. In both cohorts 58.6% were female. The most frequent indication for treatment was respiratory disease (40%). The relative rate of nonvertebral fracture during oral corticosteroid treatment was 1.33 (95% confidence interval [CI], 1.29-1.38), that of hip fracture 1.61 (1.47-1.76), that of forearm fracture 1.09 (1.01-1.17), and that of vertebral fracture 2.60 (2.31-2.92). A dose dependence of fracture risk was observed. With a standardized daily dose of less than 2.5 mg prednisolone, hip fracture risk was 0.99 (0.82-1.20) relative to control, rising to 1.77 (1.55-2.02) at daily doses of 2.5-7.5 mg, and 2.27 (1.94-2.66) at doses of 7.5 mg or greater. For vertebral fracture, the relative rates were 1.55 (1.20-2.01), 2.59 (2.16-3.10), and 5.18 (4.25-6.31), respectively. All fracture risks declined toward baseline rapidly after cessation of oral corticosteroid treatment. These results quantify the increased fracture risk during oral corticosteroid therapy, with greater effects on the hip and spine than forearm. They also suggest a rapid offset of this increased fracture risk on cessation of therapy, which has implications for the use of preventative agents against bone loss in patients at highest risk.